(untitled) (Raparin Journal of Humanities (RJH), 2020)
This research seeks to find the relation between the concepts of (socialization, political awareness, and social media), Then, it focuses on the first emergence of social Medias, for finding the properties and the importance of their role in the social relations and people’s lives. After that, we want to know to what extent the social relationship has the effect on the political awareness of the individuals and what happens next, is there a reason for the people to ask for their rights, or the world leader’s abuse this factor for their interest. In (2020) around (15) years on the appearance of social medias, This means the companies have collected the data fifteen years of their users from the picture, video, click, post, share, location, job, Hobby, etc. It has expected that via the analysis of the data, before the election the political background of the people is going to be known. Furthermore, their lifestyle is is going to be known. This leads to political change all over the world.